Ruptured mediastinal pseudocyst with pancreaticopleural fistula formation in a 15-year-old boy presenting with white-out hemithorax: A case report (Indian Journal of Case Reports, 2021)
Pancreaticopleural fistula (PPF) is a rare complication of chronic pancreatitis described more commonly in adults with alcoholic and necrotizing pancreatitis. We report a rare case of ruptured mediastinal pseudocyst with the formation of PPF in a 15-year-old boy who presented with progressive dyspnea and large left-sided pleural effusion that recurred despite repeated drainage. On the basis of imaging findings and pleural fluid analysis, the diagnosis of PPF with ruptured mediastinal pseudocyst was made. The diagnosis of PPF should be considered in patients with non-resolving large left-sided pleural effusions. The diagnosis can be confirmed either by significantly raised amylase levels in pleural fluid or direct visualization of the fistula on Computed tomography/magnetic resonance cholangiopancreatography.